Virtual reality and music's impact on psychological well-being - Alexanian, Stephen; Foxman, Maxwell; Pimentel, Danny (Frontiers in Rehabilitation Sciences, 2022)
Quality of life is bound to psychological well-being, which in turn is affected by the frequency and magnitude of negative mood states. To regulate mood states, humans often consume media such as music and movies, with varied degrees of effectiveness. The current investigation examined the effectiveness of virtual reality (VR) vs. two-dimensional (2D) online interventions with various stimuli (audiovisual vs. visual only vs. audio only) to assess which interventions were most effective for improved well-being. Additionally, this study examined which groups displayed the highest amount of perceived presence to understand what components are essential when maximizing a person's subjective feeling of being “in” a new place and if this translated toward therapeutic results. Our data suggests that even though VR participants generally experienced more presence and had similar benefits as 2D groups for increasing positive mood, only participants in the 2D groups had a reduction in negative mood overall with 2D audiovisual participants experiencing the best results. These results contradict past studies which indicate that there could be other psychological and theoretical considerations that may play a role in determining what online experiences are more effective than just examining presence and immersive stimuli. Further research and development into using VR as a tool for improved well-being is needed to understand its efficacy in remote and in-person setting.